Development of Smart-ArabAR Immersive Learning Media with 3D Augmented Reality Technology - Amit Dana Ikmah; Muhammad Taufiq; Muhammad Thoriqul Islam (Journal of Arabic Language Teaching, 2026)
The scarcity of interactive and immersive instructional media in Arabic language education has led to low student engagement and fragmented mastery of the four core skills: listening, speaking, reading, and writing. Grounded in constructivist and socio-constructivist learning theories, which emphasize active knowledge construction and social interaction, this gap calls for technology-enhanced solutions. This study aims to develop and evaluate Smart-ArabAR, an innovative learning application that integrates 3D Augmented Reality and artificial intelligence to provide adaptive, personalized, and immersive Arabic learning experiences. Using a Research and Development approach with a modified 3D model (Define, Design, Develop) derived from Thiagarajan’s 4D framework, the product was validated through questionnaires administered to one media expert and one material expert across two evaluation stages, involving first-semester students from the PBA, PAI, and PGMI programs. The findings reveal that Smart-ArabAR is highly feasible and appropriate for use, successfully integrating all four language competencies within an interactive 3D AR environment. In conclusion, Smart-ArabAR strengthens the effectiveness of AR-based Arabic pedagogy and offers a practical solution to bridge digital divides in online and hybrid learning. It is recommended that further implementation be expanded to more institutions and that longitudinal studies be conducted to assess long-term impacts on language proficiency. Minimnya media pembelajaran yang interaktif dan imersif dalam pendidikan bahasa Arab mengakibatkan rendahnya keterlibatan siswa dan penguasaan yang terfragmentasi pada empat keterampilan inti: menyimak, berbicara, membaca, dan menulis. Berlandaskan teori belajar konstruktivis dan sosio-konstruktivis yang menekankan konstruksi pengetahuan aktif dan interaksi sosial, kesenjangan ini menuntut solusi berbasis teknologi. Penelitian ini bertujuan mengembangkan dan mengevaluasi Smart-ArabAR, sebuah aplikasi pembelajaran inovatif yang mengintegrasikan Augmented Reality 3D dan kecerdasan buatan untuk menyediakan pengalaman belajar bahasa Arab yang adaptif, personal, dan imersif. Menggunakan pendekatan Penelitian dan Pengembangan dengan model 3D (Define, Design, Develop) yang dimodifikasi dari model 4D Thiagarajan, validasi produk dilakukan melalui kuesioner oleh satu ahli media dan satu ahli materi dalam dua tahap evaluasi, melibatkan mahasiswa semester pertama program studi PBA, PAI, dan PGMI. Temuan menunjukkan bahwa Smart-ArabAR dikategorikan sangat layak dan sesuai digunakan, berhasil mengintegrasikan keempat kompetensi bahasa dalam lingkungan AR 3D yang interaktif. Kesimpulannya, Smart-ArabAR meningkatkan efektivitas pedagogi bahasa Arab berbasis AR dan menawarkan solusi praktis untuk menjembatani kesenjangan digital dalam pembelajaran daring dan hibrida. Direkomendasikan agar implementasi lebih lanjut diperluas ke lebih banyak institusi dan dilakukan studi longitudinal untuk menilai dampak jangka panjang terhadap kemahiran berbahasa.